2017
DOI: 10.7860/jcdr/2017/28793.10632
|View full text |Cite
|
Sign up to set email alerts
|

Audit of Organic Acidurias from a Single Centre: Clinical and Metabolic Profile at Presentation with Long Term Outcome

Abstract: OA is part of differential diagnosis in sick children and treatment needs to be prompt and specific. Prognosis is guarded even with long term cofactor supplementation in the symptomatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…PA and MMA cause life‐threatening metabolic decompensation episodes and can result in serious sequelae. Although early detection with expanded newborn screening protocols and improvements in conventional substrate reduction therapy have led to an overall decrease in mortality, growth retardation and failure, poor nutritional status, selective organ impairment, and accumulative neurologic injury are persistent disease complications …”
Section: Discussionmentioning
confidence: 99%
“…PA and MMA cause life‐threatening metabolic decompensation episodes and can result in serious sequelae. Although early detection with expanded newborn screening protocols and improvements in conventional substrate reduction therapy have led to an overall decrease in mortality, growth retardation and failure, poor nutritional status, selective organ impairment, and accumulative neurologic injury are persistent disease complications …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, results showed that patients would be more susceptible to develop behavioral disorders such as self-damaging or self-regulating issues, anxious and avoidant behaviors, confirmed by parents [ 11 ]. Those behavioral signs are concordant with the higher prevalence of neurodevelopmental disorders in organic acidurias [ 18 ]. Concerning PA, the most frequent disorders are neurodevelopmental disorders from the Autism Spectrum ([ 5 , 21 ].…”
Section: Introductionmentioning
confidence: 69%
“…Indeed, borderline personality traits and dissociative symptoms are associated with sexual and physical abuse and emotional neglect (de Aquino [ 1 ]). In addition, one could suppose that propionic acidemia is associated with an emotional dysregulation, as suggested by previous literature in children and young adults with PA or others organic acidurias [ 11 , 13 , 18 ]. This issue of self-regulation could lead to an hyperreactivity to traumatic events.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Vitamin B 12 responsive MMAs have favourable outcomes with early diagnosis 15 and in our own experience. 16 …”
Section: Global Health Problem Analysismentioning
confidence: 99%